Safety management of the existing road network - Budzyński, Marcin; Jamroz, Kazimierz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The objective of road infrastructure safety management is to ensure that when roads are planned, designed, built and used traffic accident risks can be identified, assessed and mitigated. There is a number of approaches, methods and tools for road safety infrastructure management. European Union Directive 2008/96/EC regulates and proposes a list of tools for managing road infrastructure safety. The paper presents two of these tools - classification of dangerous sections and control of the infrastructure in the field of safety. The final section presents the necessary directions for further action, particularly scientific research, supporting the management of the existing road infrastructure.